Long-term disease-free survival after breast cancer metastatic to the ovary. Issue 3 (1st April 2002) - Zehetleitner, G; Thiel, I; Petru, E
Abstract : Abstract: Zehetleitner G, Thiel I, Petru E. Long-term disease-free survival after breast cancer metastatic to the ovary. The prognosis of patients with breast cancer symptomatically metastatic to the ovary is almost uniformly poor. In this case report, we present a 33-year-old para-4 with a symptomatic metastasis to the ovary. Previously, a modified radical mastectomy with adjuvant radiotherapy had been performed for invasive ductal carcinoma of the left breast. Laparotomy showed a 13-cm tumor of the left ovary; frozen section histology showed malignancy consistent with the previous breast cancer. The patient received adjuvant combination chemotherapy. About 5 years later, a carcinoma of the right breast was treated with conservative surgery and adjuvant radiation and chemotherapy. After a further 4 years, a recurrence at the left chest wall was treated with radiation. At the last follow-up, more than 13 years after the first breast cancer and 12 years after the ovarian metastasis, the patient was alive and well without evidence of disease. Bilateral oophorectomy is a therapeutic option in premenopausal patients with localized or advanced breast cancer. Our patient experienced long-term disease-free survival following an isolated metastasis to one ovary. This represents the first report of long-term survival of such a patient in the literature.